Volitional strategies used by university students in different learning styles - Juárez Díaz, Catalina; Rodríguez Guardado, María del Socorro (IE Revista de Investigación Educativa de la REDIECH, 2022)
The objective of this research was to identify the volitional strategies that university students with different learning styles implement. Hence, learning styles and volitional strategies were distinguished. After that, the different volitional strategies used by students with different learning styles were determined. The study was qualitative; the phenomenological method was used to understand the students’ experiences when using volitional strategies according to their learning style. The participants were 47 women (58%) and 34 men (42%) from a public university in the State of Puebla, aged between 18 and 48 years (M = 21.67; SD = 4.91). However, only 18 students were interviewed. The CHAEA questionnaire was used to identify the learning styles and an interview, previously validated, included four categories: Motivation control, Emotion control, Behavior control, and Environment control. The results obtained showed that the strategies most used by the students were those of behavior, followed by those of motivation and emotion. The least mentioned was the environmental control strategy. It is suggested to introduce in the teaching and learning process the development and strengthening of these strategies to favor the students’ academic achievement.